(untitled) (Fiep Bulletin - online, 2014)
Introduction: Patients with Coronary Artery Disease, both in its acute forms as chronic, have high levels of inflammatory adipokine interleukin-6 (IL-6) compared with the general population, presumably healthy. Interleukin-6 is a multifunctional cytokine that regulates body’s immune response, hematopoiesis, acute phase response and inflammation. In skeletal muscle, the expression of IL-6 increases after physical exercise and is expressed by the muscle fibers during contraction being released in large quantities into the circulation of the muscle during the practice. Methods: Cross-sectional study controlled based on a historical sample obtained by drawing lots among the records of the database of patients with metabolic syndrome, according to the absence or presence of established cardiovascular disease, classified according to the NCEP/ATP III, the Outpatient Risk Cardiometabolic Hospital PUCRS, from 03/2008-12/201. Conclusion: IL-6 is involved in the pathogenesis of metabolic syndrome and the association of clinical cardiovascular outcomes. For the two groups of sedentary and physically active regularly, statistical significance was obtained, however, it is known that the sample used for this analysis has little statistical power.